Optimization of Interactive Multimedia to Enhance Students’ Cognitive Development through Islamic Religious Education - Disti Liana; Melisa Novianty; Efan Efan; Yadi Yadi (CV. Media Inti Teknologi, 2025)
Background: Islamic Religious Education (IRE) plays a crucial role in shaping students’ character at the elementary level. However, traditional learning methods often limit student engagement and independent learning.Aims: This study aims to develop and validate interactive multimedia for IRE aligned with the Merdeka Curriculum, focusing on cognitive enhancement and Islamic character formation.Method: The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants included 30 upper-grade elementary students and 5 IRE teachers. Instruments consisted of expert validation rubrics (content, usability, benefit, and technical aspects) and practicality questionnaires. Content validity was analyzed using Aiken’s V, while reliability was measured with Cronbach’s alpha. Ethical clearance and consent from participants were obtained.Results: The multimedia was validated by experts with an average Aiken’s V of 0.87 (valid) and practicality rated by teachers and students with a Cronbach’s α of 0.89 (good reliability). The average practicality percentage reached 85.75%, categorized as very practical. Annotated screenshots show labeled UI features such as transliteration toggles, audio controls, and navigation bars, supporting accessibility and engagement.Conclusion: The developed multimedia has been validated and proven practical for classroom use. While findings confirm feasibility and usability, its effectiveness in improving learning outcomes requires further experimental testing.